Small-Sided Soccer Game (1v1) in Goalkeepers' Training - Dawid Goliński; Jarosław Muracki; Paweł Wolański; Sebastian Klich; Eugenia Murawska-Ciałowicz (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
Small-sided soccer games, i.e. 1v1 are often used in training, which results in a composite influence on the player. Training exercises stimulated in the game allow to master many skills, form habits and modify behaviors associated with solving specific situations during a match. The aim of the study was to assess the intensity of exercise during a 1v1 game for goalkeepers. Eight goalkeepers participated in the experiment (body weight 80.63 ±3.50 kg, body height 184.69 ±3.71 cm, BMI 23.64 ±0.74). All goalkeepers played 1v1 games. During the small-sided game players can use all the goalkeeper techniques to score a goal. During all of the matches, heart rate (HR) was recorded using a sport tester, LA was measured in the second minute after the end of each game. There was also collected data determining subjective assessment of the effort made by the players using Borg scale (RPE). The highest average HR and RPE were recorded in the third match, respectively (192.38 ±8.07 b/min; 14.38 ±2.07), while in the first match the examined parameters were on average 186 ±8.85 b/min; 11.38 ±1.51, and in the second 186.00 ±8.09 b/min; 13.50 ±1.85 respectively. The highest LA level was recorded after the second match and equaled 7.71 ±2.07 mmol/l (7.06 ±3.54 after the first match and 7.5 ±1.37 after the third match). The 1v1 game requires the use of similar to the real game actions, as well as the average exercise intensity is also similar to the scoringopportunity situations and conditions of a match.